Playing the Online Games Becomes One of Affecting Factors to Generate the Second Language Acquisition (SLA) for Millennials - Asih Prihandini (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research aims to analyze how playing online games could be one of affecting factors to generate the second language acquisition to millennial. It’s a case study to a child living in multilingual environment where some languages used, they are Indonesian, Sundanese and English. Online games are mostly played by using English as the communication tool which in this research English is the second language comprehended. Some factors such as the participants, solidarity and status among the players affect to the child in comprehending his second language that is English. He switches the language following the topic he’s speaking. That condition guides him to be able to speak English well. His comprehension about lexical English has been coloring his own linguistic repertoire that is Indonesian. Some theories used relating with this research are Sociolinguistics and Second Language Acquisition (SLA). The data are analyzed and described qualitatively. Some results obtained are (1) modelling variety or code choice used, and (2) linguistics constraints found. The modelling variety or code chosen are Indonesian and English where the discourse domain is when the child is playing the online games at home. The situational and linguistic context must be appropriate to the choice of code used in the community. Afterwards some codes chosen, those are Indonesia and English could be constraint linguistically. This conditions show that how playing online games could give good impact for millennials in improving their second language acquisition